As vozes do “eu” das personagens femininas se Elvira Vigna - Silva, Kézia Divina de Oliveira Castilho (2023)
This thesis is the result of a bibliographic research, with a qualitative approach to analyze female representations from a gender perspective, understanding the issue of the female figure in the reproduction or reconstruction of her role in society. The general objective was: to discuss the representation of the female characters of Elvira Vigna in the works: like we´re on bitch palimpsest of whores and Nothing to say, in the perspective of gender. The author outlines her texts by deconstructing and reconstructing multiple female identities, subjects of the plot, and one of the resources most used by her, to invert social roles and empower woman, is the creation of narrators-protagonists who give voice to the yearnings, fears and their aspirations and, even more, they seek to understand themselves despite confrontations and social impositions. It was described as the author, representative of contemporary literature, seeks to deconstruct androcentric patterns of gender roles, portraying the female image with new perspectives. for this purpose, she builds a fragmented narrative, a first-person narrative, to tell her perception as a reader, “the pair of ears of João, who listens to the cases reported by him, and that of the narrator who tells João’s stories with all the the gaps left by him, and there are many, he fills these gaps using his experiences and narrates the story with all his subjectivity to his readers.The works of the study are considered instruments of resistance, in which the author's voice questions social and family contexts, arrogance, power, submission, in relation to traditional female roles, as well as invisibility in relationships with others